Pharmacist attire and its impact on patient preference - Cretton-Scott E; Johnson L; King S (Centro de Investigaciones y Publicaciones Farmaceuticas, 2011)
Objective: To determine the influence of demographics on patient preferences for community pharmacist attire.Methods: A 10-item questionnaire was developed and administered to patients visiting a chain pharmacy or an independent pharmacy in the Birmingham, Alabama metropolitan area. Mann-Whitney was used to examine if statistical differences existed in chain versus independent pharmacy patient's selections based on pharmacist attire.Results: A statistically significant difference in patient preference for pharmacist attire between the settings in regards to which pharmacist patients felt was more approachable was observed; 51.2% of chain pharmacy respondents compared to 30% of independent pharmacy respondents identified the pharmacist pair with business formal attire and white coat as more approachable. Differences in education was also apparent with 70% of respondents in the independent pharmacy setting reporting having a Bachelor's degree or higher compared to 45% of respondents in the chain pharmacy setting.Conclusion: With the exception of approachability, patients indicated preference for pharmacist with the white coat regardless of community setting. Given the importance of patient-pharmacist communication for building successful patient-pharmacist relationships, if patients do not perceive the pharmacists as approachable, communication and subsequent development of said relationships may not occur regardless of perceived knowledge and competency.